Massive endocytosis driven by lipidic forces originating in the outer plasmalemmal monolayer: a new approach to membrane recycling and lipid domains - Fine, Michael (The Rockefeller University Press, 2011)
The roles that lipids play in endocytosis are the subject of debate. Using electrical and imaging methods, we describe massive endocytosis (MEND) in baby hamster kidney (BHK) and HEK293 cells when the outer plasma membrane monolayer is perturbed by the nonionic detergents, Triton X-100 (TX100) and NP-40. Some alkane detergents, the amphipathic drugs, edelfosine and tamoxifen, and the phospholipase inhibitor, U73122, are also effective. Uptake of the membrane tracer, FM 4–64, into vesicles and loss of reversible FM 4–64 binding confirm that 40–75% of the cell surface is internalized. Ongoing MEND stops in 2–4 s when amphipaths are removed, and amphipaths are without effect from the cytoplasmic side. Thus, expansion of the outer monolayer is critical. As found for Ca-activated MEND, vesicles formed are <100 nm in diameter, membrane ruffles are lost, and β-cyclodextrin treatments are inhibitory. However, amphipath-activated MEND does not require Ca transients, adenosine triphosphate (ATP) hydrolysis, G protein cycling, dynamins, or actin cytoskeleton remodeling. With elevated cytoplasmic ATP (>5 mM), MEND can reverse completely and be repeated multiple times in BHK and HEK293 cells, but not cardiac myocytes. Reversal is blocked by N-ethylmaleimide and a nitric oxide donor, nitroprusside. Constitutively expressed Na/Ca exchangers internalize roughly in proportion to surface membrane, whereas Na/K pump activities decrease over-proportionally. Sodium dodecyl sulfate and dodecylglucoside do not cause MEND during their application, but MEND occurs rapidly when they are removed. As monitored capacitively, the binding of these detergents decreases with MEND, whereas TX100 binding does not decrease. In summary, nonionic detergents can fractionate the plasma membrane in vivo, and vesicles formed connect immediately to physiological membrane-trafficking mechanisms. We suggest that lateral and transbilayer inhomogeneities of the plasma membrane provide potential energies that, when unbridled by triggers, can drive endocytosis by lipidic forces.